2020
DOI: 10.31812/123456789/4121
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence plot-based analysis of financial-economic crashes

Abstract: The article considers the possibility of analyzing the dynamics of changes in the characteristics of time series obtained on the basis of recurrence plots. The possibility of using the studied indicators to determine the presence of critical phenomena in economic systems is considered. Based on the analysis of economic time series of different nature, the suitability of the studied characteristics for the identification of critical phenomena is assessed. The description of recurrence diagrams and characteristi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…xlii This article highlights further research by the authors, begun in [36,45,46,73,182,196,210,236].…”
Section: Session 5: Cloud-based E-learning Platforms Tools and Servicesmentioning
confidence: 94%
“…xlii This article highlights further research by the authors, begun in [36,45,46,73,182,196,210,236].…”
Section: Session 5: Cloud-based E-learning Platforms Tools and Servicesmentioning
confidence: 94%
“…xvii This article highlights further research by the authors, begun in [16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33]. The focus of the article "Irreversibility of financial time series: a case of crisis" [34] by Andrii O. Bielinskyi, Serhii V. Hushko (figure 5), Andriy V. Matviychuk, Oleksandr A. Serdyuk, Serhiy O. Semerikov and Vladimir N. Soloviev to measure the varying irreversibility of stock markets.…”
Section: Articles Overviewmentioning
confidence: 96%
“…Authors detected phase transitions when market transforms from bull state to bear state. Soloviev et al (2020) analyzed 9 critical periods in the Dow Jones Industrial Average (DJIA) index for the period between 1 January 1990 and 1 June 2019 by using sliding window RQA. Authors demonstrated that during all critical periods RQA measure DET shows a downward trend and can detect critical phenomenon.…”
Section: Literature Reviewmentioning
confidence: 99%